Controlled preparation of a novel GNP@MgO particles and its refinement mechanism in Mg-9Al alloy - Shuaihu Wei; Xiaojun Wang; Xuejian Li; Hailong Shi; Xiaoshi Hu; Chao Xu (Journal of Magnesium and Alloys)
The addition of effective nucleating particles in the melt to achieve grain refinement has become the most widely used method for the casting industries. In this study, a novel GNP@MgO particle with a nanocomposite structure was prepared by utilizing an in-situ reaction of the carbon source gas with Mg melt. The results showed that the particles can significantly reduce the average grain size of Mg-9Al alloy from 130.4 µm to 13.1 µm, and achieve an ultra-high grain refinement efficiency of 90%. The refinement mechanisms are that the Al4C3 phase can act as a heterogeneous nucleation site for α-Mg grains due to the orientation relationship as (001)Al4C3//(002)Mg. Meanwhile, the particle distribution model shows that the velocity of MgO particles is much higher than the growth rate of α-Mg grains. Therefore, it is pushed to the vicinity of grain boundaries during solidification, effectively limiting the growth of α-Mg grains. The remarkable grain refinement effect was achieved through the synergistic modulation of Al4C3 and MgO particles. This work may provide new insight into designing high efficiency grain refiners for Mg-Al alloys.